Understanding The Effects Of Garcinia Atroviridis Essential Oils In Combination With 2-Deoxy-D-Glucose On Pancreatic Cancer Cells (Panc 1) - Aziz, Fatin Athirah Abdul (2020)
Pancreatic cancer is among the highest lethal cancer in the world and current treatment and biomarker for this cancer is still limited. This study aimed to investigate the anti-proliferative effects of essential oils extracted from the leaves (EO-L) and stem bark (EO-B) of Garcinia atroviridis against human pancreatic cancer cell line, PANC- 1. The selective index (SI) values of each treatment was determined based on the ratio of IC50 in BEAS-2B cells in comparison to PANC-1 cells. In PANC-1 cells, IC50 and SI values of EO-L was 78 μg/ml and 1.23, respectively. EO-L at 100 μg/ml concentration had induced 73.97% the release of LDH after 24 h of incubation period. On the contrary, EO-B showed no pronounced anti-proliferative effect. Combination treatment between EO-L and 2-DG showed moderate synergism, with combination index (CI) values of 0.36 to 0.75. The effects of EO-L, 2-DG and EOL+2DG were further investigated on mitochondrial membrane potential (MMP), apoptosis, cell cycle and mRNA expression of selected regulatory molecules involved in apoptosis and cellular metabolism. EO-L had induced 57.9% MMP and 49.7% apoptosis in PANC-1 cells after 24 h of treatment. At 72 h of treatment, 2-DG and EOL+2DG caused 47.6% and 60.8% of MMP, respectively. Both 2-DG and EOL+2DG had caused PANC-1 cells to undergo apoptosis by 18.1% and 63.1%, respectively. Further, EO-L had induced 24.5% accumulation of cells at S phase after 48 h of treatment. At 24 h treatment, 2-DG and EOL+2DG had induced PANC-1 cells to be accumulated at G1 phase by 60.77% and 70.9%, respectively.